ALGORITMA DETEKSI FREKUENSI DTMF MENGGUNAKAN KORELASI SILANG UNTUK TELEKOMANDO WAHANA TERBANG (DTMF FREQUENCY DETECTION ALGORITHM USING CROSSCORRELATION FOR VEHICLE TELECOMMAND) - Kliwati , Sri (BRIN Publishing, 2016)
In general, the frequency DTMF detection algorithm using FFT (Fast Fourier Transform) and Goertzel Algorithm. However, in certain circumstances a more suitable signal detected by the other algorithms. For example in a non-periodic signal as the measurement sensors for flight vehicle. The purpose of this study is to develop a system telecommand for flight vehicle. And this paper discusses the frequency DTMF (Dual Tone Multi Frequency) detection method using cross correlation algorithm and data-base DTMF. The simulation results show the frequency detection successfully carried out in accordance with the accuracy of the data-base created (1 Hz) to change the frequency of zero to 1700 Hz (DTMF frequency limit).